Tata kelola pemerintahan dinamis pada implementasi kebijakan inovasi pelayanan - Ira Patriani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Because of their variety, service innovation policy implementation issues are interesting to research. This study investigates, describes, and analyses the Pontianak City Population and Civil Registration Office's dynamic governance implementation of novel population administration service policies. This research describes phenomena using descriptive qualitative research methodologies based on interviews, observations, literature studies, and other pertinent data. The results of this study indicate that population administration service innovation is still constrained by the limited quantity of resources in the IT field for online service implementation. The interpreters' policy grasp is good, but the community lacks socialisation. Application activities show how these operations are still inflexible and less preventive, making technical problem solving even for normal organisational actions less anticipatory. This study concludes that the Population and Civil Registration Office of Pontianak City's Service Innovation Policy implementation is dynamic in work governance, including organisational activities, interpretation, and application. Researchers propose creating and sharing SOPs, hiring IT leaders, training personnel, monitoring, evaluating, maintaining website servers, and improving workplace internet speed as needed.